2022
DOI: 10.3233/bd-210071
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on pathological complete response and survival of breast cancer patients receiving neoadjuvant chemotherapy

Abstract: BACKGROUND: High body mass index (BMI) is regarded as a poor prognostic factor in breast cancer (BC). However, its association with pathological complete response (pCR) and survival after neoadjuvant chemotherapy (NAC) remains controversial. OBJECTIVE: We wanted to assess the prognostic impact of BMI in this setting. METHODS: Single-center, retrospective review of 314 BC patients undergoing NAC from 2010 to 2018. Patients were categorized as underweight/normal weight (UW/NW) (BMI < 25) or overweight/obese (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…There seems to be evidence from the numerous studies of the association of BC with obesity, which warrants further prospective research. Studies have reported that BMI was not found to influence the rate of pCR (16,17). On the contrary, in other studies, it was found that obesity had a negative impact on pCR.…”
Section: Obesitymentioning
confidence: 88%
“…There seems to be evidence from the numerous studies of the association of BC with obesity, which warrants further prospective research. Studies have reported that BMI was not found to influence the rate of pCR (16,17). On the contrary, in other studies, it was found that obesity had a negative impact on pCR.…”
Section: Obesitymentioning
confidence: 88%